Teacher workload in Australia: National reports of intensification and its threats to democracy - Gavin, Mihajla; McGrath-Champ, Susan; Wilson, Rachel; Fitzgerald, Scott; Stacey, Meghan (Routledge, 2021)
The recent reforms of education, driven by neoliberal logics of choice, competition and autonomy, have fundamentally challenged the importance of education and schooling as core to the healthy functioning of socio-democratic societies. Little attention has been paid, however, to how the de-democratisation of education is affecting the work of teachers as educators. Drawing on data from a series of systematic and comparable large-scale surveys (N=48,000), we draw attention to the stark reality of teachers’ work today in the context of Australia. The most prominent finding is the documentation of the universal intensification of teachers’ work and explosion of teachers’ working hours driven by instruments of compliance, datafication and diminution of time to get on with the core job of teaching. We reflect upon how intensification of teachers’ work threatens the democratic purposes of schooling, and argue for system-level monitoring and evaluation to inform policy-making to challenge de-democratising practices.